Nutrient modulation in the management of disease-induced muscle wasting: evidence from human studies - Brook, Matthew S.; Wilkinson, Daniel J.; Atherton, Philip J. (Lippincot, Williams & Wilkins, 2017)
Purpose of review: In addition to being essential for movement, skeletal muscles act as both a store and source of key macronutrients. As such, muscle is an important tissue for whole body homeostasis, undergoing muscle wasting in times of starvation, disease, and stress, for example, to provide energy substrates for other tissues. Yet, muscle wasting is also associated with disability, comorbidities, and mortality. As nutrition is so crucial to maintaining muscle homeostasis 'in health', it has been postulated that muscle wasting in cachexia syndromes may be alleviated by nutritional interventions. This review will highlight recent work in this area in relation to muscle kinetics, the acute metabolic (e.g. dietary protein), and longer-term effects of dietary interventions.